A COMPARATIVE STUDY ON THE ACCURACY OF THE TRANSLATION OF ENGLISH NARRATIVE TEXT INTO INDONESIAN USING GOOGLE TRANSLATE AND CHAT GPT AI - Triana, Devi; Sembiring, Yena Jorena; Lumbantobing, Nessa Tri Fanny; Sihaloho, Angel Lamtama; Sinurat, Bloner (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
This study employs a descriptive qualitative method to compare the accuracy of translating two narrative texts from English into Indonesian using Google Translate and ChatGPT. The narrative texts were sourced from Detik.com and translated using both tools. The goal of this study is to evaluate grammatical precision, contextual consistency, and fluency in the translations. The findings reveal that ChatGPT excels in maintaining context and coherence, delivering more accurate and natural translations compared to Google Translate. Google Translate tends to be less accurate, particularly when handling more complex contexts. These findings suggest that ChatGPT can provide more reliable and relevant translations, particularly for communication and language learning purposes.